2012
DOI: 10.1007/s00299-012-1276-2
|View full text |Cite
|
Sign up to set email alerts
|

Rice choline monooxygenase (OsCMO) protein functions in enhancing glycine betaine biosynthesis in transgenic tobacco but does not accumulate in rice (Oryza sativa L. ssp. japonica)

Abstract: Expression and transgenic studies demonstrate OsCMO is transcriptionally induced in response to salt stress and functions in increasing glycinebetaine accumulation and enhancing tolerance to salt stress. Immunoblotting analysis suggests that no accumulation of glycinebetaine in the Japonica rice plant presumably results from lack of a functional OsCMO protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 49 publications
3
20
0
Order By: Relevance
“…In addition to its protective roles in enzyme and membrane integrity, the expression of related genes is also affected by exogenous GB, and these genes are mainly involved in the biosynthesis and metabolism pathway of GB and phytohormones. It has been shown that CMO plays an important role in the pathway of glycine betaine synthesis (Burnet et al, 1995) and responses to abiotic stresses in rice (Luo et al, 2012), which are consistent with our results. Our study showed that the upregulated expression of the CMO gene in drought-stressed plants with GB pretreatment was concomitant with the accumulation of exogenous glycine betaine and an increase in BADH activity.…”
Section: Discussionsupporting
confidence: 93%
“…In addition to its protective roles in enzyme and membrane integrity, the expression of related genes is also affected by exogenous GB, and these genes are mainly involved in the biosynthesis and metabolism pathway of GB and phytohormones. It has been shown that CMO plays an important role in the pathway of glycine betaine synthesis (Burnet et al, 1995) and responses to abiotic stresses in rice (Luo et al, 2012), which are consistent with our results. Our study showed that the upregulated expression of the CMO gene in drought-stressed plants with GB pretreatment was concomitant with the accumulation of exogenous glycine betaine and an increase in BADH activity.…”
Section: Discussionsupporting
confidence: 93%
“…As discussed in the Introduction, choline is also used for GB synthesis catalysed by CMO and BADH (Annunziata, Ciarmiello, Woodrow, Dell'Aversana, & Carillo, ). Overexpressing OsCMO in tobacco plants increased GB content and improved plant salt tolerance (Luo et al, ). Overexpression of the AhBADH gene isolated from Atriplex hortensis improved salt tolerance in trifoliate orange ( Poncirus trifoliata L.…”
Section: Discussionmentioning
confidence: 99%
“…Non-accumulators, such as Arabidopsis and rice also have the Reiske-type and mononuclear non-heme clusters. However, they exhibit mutations at other residues considered functionally important (e.g., in Arabidopsis CMO; Hibino et al 2002), or process incorrect and shorter transcripts (e.g., rice CMO; Luo et al 2012), and vary significantly at their N-terminal end (Fig S1). Iron-sulfur (Reiske) clusters are involved in vital processes, such as cell respiration and photosynthesis due to their ability to transfer electrons, and have other functions, such as centres of catalytic activity, regulators of gene expression (in bacteria), and sensors of iron and oxygen (reviewed in Balk & 892 S. Joseph et al Lobreaux 2005).…”
Section: Discussionmentioning
confidence: 99%
“…S1). It is notable that Arabidopsis and cereals, such as rice, are known low or non-GB accumulators (Hibino et al 2002;Luo et al 2012) and do not exhibit the AVA residues at the start of the mature polypeptide determined experimentally in spinach (Rathinasabapathi et al 1997), raising the question whether their CMO pre-proteins are processed correctly.…”
Section: Discussionmentioning
confidence: 99%